THE CONSEQUENCES OF OCCUPATIONAL STRESS IN 21st CENTURY COMPANIES - dos Santos, Isabela Mastriani; Santos, Natalia Cristina Rodrigues; da Costa, Elvio Carlos (Revista Interface Tecnológica, 2023)
The main objective of this article was to identify the causes that lead to occupational stress in employees and to raise the possible physical and emotional consequences, and in view of this, it was analyzed how the organization acts through this conflict and what initiatives it implements to minimize the negative effects. It also had the intention of showing how important an early diagnosis is so as not to result in damage to health. The methodology used was a bibliographic survey in the most relevant database of scientific works already carried out and as a data collection instrument a questionnaire with 11 questions was applied to 74 participants from the city of Araraquara and region, in order to identify the reality of the professional life of each individual in relation to the scenario caused by occupational stress and the illnesses left by this evil. We obtained as results that the employee needs to be well mentally and physically, to deliver positive results and the organization must be attentive and concerned with the quality of life of each individual.